2015
DOI: 10.1002/acr.22546
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Posterior Heel Pain in the General Population: Cross‐Sectional Findings From the Clinical Assessment Study of the Foot

Abstract: ObjectiveTo identify the population prevalence of posterior heel pain (HP), related disability, and associated factors.MethodsA total of 9,334 adults ages ≥50 years were mailed a questionnaire. Participants reporting foot pain in the last month shaded the foot pain location on a manikin. The Manchester Foot Pain and Disability Index assessed disabling foot pain. Population prevalence of any, bilateral, and disabling posterior HP was estimated using weighted logistic regression accounting for nonresponse. Odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
6
18
2
2
Order By: Relevance
“…Cluster 1 (forefoot, toe, and nail) had the highest proportion of older people, those with arthritis, and those with diabetes mellitus. Age , arthritis , and diabetes mellitus have all been shown to be associated with foot pain, and the age‐related increased prevalence of foot deformities, such as hallux valgus, may also partly explain this pattern . While Chatterton et al found an association between posterior heel pain and diabetes mellitus, which may be due to Achilles tendon involvement, the current study found an association between forefoot pain and diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Cluster 1 (forefoot, toe, and nail) had the highest proportion of older people, those with arthritis, and those with diabetes mellitus. Age , arthritis , and diabetes mellitus have all been shown to be associated with foot pain, and the age‐related increased prevalence of foot deformities, such as hallux valgus, may also partly explain this pattern . While Chatterton et al found an association between posterior heel pain and diabetes mellitus, which may be due to Achilles tendon involvement, the current study found an association between forefoot pain and diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 57%
“…Age , arthritis , and diabetes mellitus have all been shown to be associated with foot pain, and the age‐related increased prevalence of foot deformities, such as hallux valgus, may also partly explain this pattern . While Chatterton et al found an association between posterior heel pain and diabetes mellitus, which may be due to Achilles tendon involvement, the current study found an association between forefoot pain and diabetes mellitus. This group also had a higher proportion of participants classified as obese, thus indicating that factors other than the response of tendons to the presence of diabetes mellitus may be a factor in the location of foot pain.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…25 On the other hand, obesity and diabetes have been identified as risk factors for posterior heel pain. 26 The risk of several rheumatic conditions is increased in patients with diabetes. 5 Tendons and ligaments, in particular, have been demonstrated to be a major target of diabetes-associated musculoskeletal damage, for example, in diffuse idiopathic skeletal hyperostosis.…”
Section: Discussionmentioning
confidence: 99%
“…e areas are concentrated in the region of the medial hindfoot and referred pain spreads throughout the medial aspect of the foot ( Figure 1). e main epidemiological studies found that 17.4% had foot pains [19], most of them in the region of the medial hindfoot [20,21]. e authors have sought anatomical approaches to support the theory of myofascial pain syndromes (MPSs) citing the presence of muscle trigger points and providing a pathophysiological explanation [6,18].…”
Section: Introductionmentioning
confidence: 99%